Development and Evaluation of a Pearl - Millet Thresher - Kamble, H G; Srivastava, A P; Panwar, J S (Journal of Agricultural Engineering, 2003)
Based on recommended design and operational parameters for pearl-millet threshing, a prototype thresher was developed and evaluated. The thresher was evaluated at three different levels each of cylinder speed (450, 700, 850 m/min), cylinder concave clearance (5, 10, 15 mm), grain moisture content (10.2, 14.5, 17.2 %) and feed rate (300, 400, 500 kg/h). The performance parameters for the study were threshing efficiency, grain damage total loss of grain, seed germination and energy consumption. The test results indicated a maximum of 96.8% threshing efficiency, a minimum of 2.75% grain damage, 2.10% total grain loss and a maximum 87% seed germination. The minimum energy consumption of 0.8 MJ per quintal of input crop was observed. The average capacity of the machine was observed to be influenced by all the study variables. The cost of operation of prototype thresher compared with traditional methods of threshing by animal trampling and manual beating were respectively Rs. 8.50, Rs. 31.25 and Rs. 165.00 per quintal of input crop. Thus, the mechanical thresher was observed to be the most economical and efficient method of pearl-millet threshing.